Albumin to globulin ratio was associated with in‐stent restenosis and revascularization events after percutaneous coronary intervention. Issue 5 (27th February 2022) - Zhang, Rui; Tao, Zaixiao; Gong, Jing; Ji, Zhenjun; Yang, Mingming; Ma, Genshan; Li, Yongjun
Abstract: In‐stent restenosis is a common complication after percutaneous coronary intervention (PCI) for coronary heart disease requiring revascularization. We performed a retrospective analysis to assess the value of inflammatory biomarker albumin to globulin ratio (AGR) in clinical prognosis of PCI. In total, 992 patients with coronary heart disease who underwent the first drug‐eluting stent implantation and re‐examination angiography in our hospital were enrolled in this study. The AGR was measured. At mean follow‐up of 11.2 ± 4 months, the in‐stent restenosis (ISR) and revascularization events (including target lesion revascularization, target vessel revascularization, and revascularization of de novo lesions) occurred in 127 and 284 patients, respectively. Compared with the non‐ISR or non‐event group, AGR was significantly lower in the ISR group and the events group. Beyond that, albumin was significantly lower, whereas urea nitrogen, glucose, and Gensini score, as well as the proportions of a history of diabetes and peripheral vascular diseases were significantly higher in the ISR group and the events group. Age, heart rate, white blood cell, neutrophils, lymphocyte, monocyte, and incidence of ischemic stroke were significantly higher in the events group. Multivariate Cox regression analysis showed that AGR was independently associated with ISR ( p = 0.032) and events ( p = 0.024). Besides, Kaplan‐Meier analysis indicated that the higher quartile of AGR had a lower rate of ISR ( p = 0.038) and events ( p ≤ 0.001). Finally, the receiver operating characteristic curve for AGR in diagnosing ISR and events indicated that the area under the curve were 0.56 and 0.57, respectively. Therefore, AGR is one of the most important factors that independently associate with the ISR and revascularization events after PCI.